Photophysical, photostability, and ROS generation properties of new trifluoromethylated quinoline-phenol Schiff bases - Rocha, Inaiá O.; Kappenberg, Yuri G.; Rosa, Wilian C.; Frizzo, Clarissa P.; Zanatta, Nilo; Martins, Marcos A. P.; Tisoco, Isadora; Iglesias, Bernardo A.; Bonacorso, Helio G. (Beilstein Journal of Organic Chemistry, 2021)
A new series of ten examples of Schiff bases, namely (E)-2-(((2-alkyl(aryl/heteroaryl)-4-(trifluoromethyl)quinolin-6-yl)imino)methyl)phenols 3, was easily synthesized with yields of up to 91% from the reactions involving a series of 2-(R-substituted) 6-amino-4-(trifluoromethyl)quinolines 1 and 4(5)-R1-substituted salicylaldehydes 2 – in which alkyl/aryl/heteroaryl for 2-R-substituents are Me, Ph, 4-MeC6H4, 4-FC6H4, 4-NO2C6H4, and 2-furyl, and R1-substituents are 5-NEt2, 5-OCH3, 4-Br, and 4-NO2. Complementarily, the Schiff bases showed low to good quantum fluorescence yield values in CHCl3 (Φf = 0.12–0.80), DMSO (Φf = 0.20–0.75) and MeOH (Φf = 0.13–0.85). Higher values of Stokes shifts (SS) were observed in more polar solvents (DMSO; 65–150 nm and MeOH; 65–130 nm) than in CHCl3 (59–85 nm). Compounds 3 presented good stability under white-LED irradiation conditions and moderate ROS generation properties were observed.
Keywords: photophysical properties; photostability; quinoline; ROS generation; Schiff base